Development of Promotional Criteria Decision Support System to Increase Sales of Scarlett Whitening Products through Digital Marketing Strategy - Frans Sudirjo; Dian Anggara Kartika Sari; Iswanto Apri Nugroho (Westscience Press, 2024)
This research delves into the multifaceted landscape of promoting skin whitening products in Indonesia, focusing on consumer behavior, digital marketing strategies, and the development of a Promotion Criteria Decision Support System (PCDSS). Through qualitative analysis of participant interviews and simulated interviews, key insights were gleaned. Consumer preferences, heavily influenced by cultural ideals, prioritize fair skin and product safety and efficacy. Digital marketing emerged as a potent tool, with social media platforms and influencer partnerships driving engagement. The necessity of a tailored PCDSS integrating cultural nuances, regulatory compliance, and consumer insights was underscored. This study provides actionable insights for skincare brands aiming to navigate the Indonesian market effectively.